Accelerated Deficits of Spatial Learning and Memory Resulting From Prenatal Inflammatory Insult Are Correlated With Abnormal Phosphorylation and Methylation of Histone 3 in CD-1 Mice - Wu, Zi-Xing; Cao, Lei; Li, Xue-Wei; Jiang, Wei; Li, Xue-Yan; Xu, Jing; Wang, Fang; Chen, Gui-Hai (Frontiers in Aging Neuroscience, 2019)
Gestational infection causes various neurological deficits in offspring, such as age-related spatial learning and memory (SLM) decline. How inflammation causes age-related SLM dysfunction remains unknown. Previous research has indicated that histone modifications, such as phosphorylation of H3S10 (H3S10p) and trimethylation of H3K9 (H3K9me3) may be involved. In our study, pregnant mice received an intraperitoneal injection of lipopolysaccharide (LPS, 50 or 25 μg/kg) or normal saline during gestational days 15–17. After normal parturition, the offspring were randomly separated into 1-, 6-, 12-, 18-, and 22-month-old groups. SLM performance was assessed using a radial six-arm water maze. The hippocampal levels of H3S10p and H3K9me3 were detected using an immunohistochemical method. The results indicated that the offspring had significantly impaired SLM, with decreased H3S10p and increased H3K9me3 levels from 12 months onward. Maternal LPS exposure during late gestation significantly and dose-dependently exacerbated the age-related impairment of SLM, with the decrease in H3S10p and increase in H3K9me3 beginning at 12 months in the offspring. The histone modifications (H3S10p and H3K9me3) were significantly correlated with impairment of SLM. Our findings suggest that prenatal exposure to inflammation could exacerbate age-related impairments of SLM and changes in histone modifications in CD-1 mice from 12 months onward, and SLM impairment might be linked to decreased H3S10p and increased H3K9me3.